The environmental fragility within the Cachoeirinha stream Hydrographic basin, in Cáceres city, Mato Grosso state (Research, Society and Development, 2022)
The objective of this study was to analyze the environmental fragility of the slope, climate, soil of and land use and cover in the Córrego Cachoeirinha hydrographic basin, located in the northeast of the municipality of Cáceres-Mato Grosso, with a focus on serving as subsidies for environmental conservation and sustainable development of the region. bowl. The methodology was defined with office and field activities. The results showed that 11.57% of the basin has very strong environmental fragility in the Serrana Province region due to the declivity above 30% and very weak fragility in 47.22% of the area in the valleys between the mountains of the Depression of the Upper Paraguay and in the Paraguay River Plain. The climate showed strong fragility for the Hot Mesothermal Altitude Tropical domain of the Meridional Facade of Chapadas and Planaltos, with rainfall from 1400 to 1600 mm in the flood season, occupying 69.16% of the highland basin region. The soil presented a very strong fragility class for the typical Eutrophic Fluvic Tb Neosol and the Eutrophic Litholic Neosol. Strong fragility was determined for typical dystrophic Tb Haplic Cambisol and leptofragmentary Dystrophic Regolithic Neosol soils and weak fragility for typical Dystrophic Red Latosol and typical Dystrophic Red-Yellow Latosol soils. The greatest weaknesses were determined on the geomorphological features of the Serrana Province, where it is necessary to use appropriate agricultural techniques that avoid impacts on the natural environment. Environmental education actions, implementation of management plans with the restoration of degraded areas are suggested.